The Impact of Refrigerated Storage on the Chemical, Physiochemical and Sensory Characteristics of Some Fruit ectars - E.Sulieman, Abdel Moneim; A. Abdalla, Rean; B. El-Hardallou, Sirelkhatim (Gezira Journal of Engineering and Applied Sciences, 2021)
This study aimed to evaluate the effect of refrigerated storage on fruit nectars prepared from: guava, mango and orange fruits. Physiochemical, chemical and sensory analysis was carried out for fresh and stored fruit nectars at 5C0. Guava nectar had the highest stability compared with orange and mango nectars, and also it had the highest value of 2.9 ± 0.04 % fiber, 0.38 ± 0.02 % fat and 199 ± 0.22 mg/100gm ascorbic acid. The mango nectar had the highest values of total soluble solids (28.2 brix). As for orange nectar, it had the highest value of protein (0.80 ± 0, 1%) and it had been changed during storage period. The sensory evaluation showed acceptance of fresh and stored fruit nectars at the second and fourth day of storage except orange nectars. which was accepted just as fresh and at second day of storage, indicating that it was more determinable than the other two fruit nectars.